Design and Outcome of a Certification Preparation Program for Outpatient Nurses. (October 2015) - Johnson, Theresa; Ferguson, Susan; McKenzie, Jennifer; Brassil, Kelly J.
<x xml:space="preserve">Abstract</x> This article presents the design, implementation, and outcomes of a certification preparation program for nurses working in an outpatient clinic. A nurse educator designed curriculum using the Certified Breast Care Nurse test blueprint. Nurse administrators provided the resources and the staff coverage to allow all staff members to attend the sessions without disruption to patient care. This outpatient center has achieved and sustained 100% certification among eligible nurses over the past 5 years.